2014
DOI: 10.1073/pnas.1400057111
|View full text |Cite
|
Sign up to set email alerts
|

Yolk-sac–derived macrophages regulate fetal testis vascularization and morphogenesis

Abstract: Organogenesis of the testis is initiated when expression of Sry in pre-Sertoli cells directs the gonad toward a male-specific fate. The cells in the early bipotential gonad undergo de novo organization to form testis cords that enclose germ cells inside tubules lined by epithelial Sertoli cells. Although Sertoli cells are a driving force in the de novo formation of testis cords, recent studies in mouse showed that reorganization of the vasculature and of interstitial cells also play critical roles in testis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
188
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(211 citation statements)
references
References 60 publications
12
188
5
Order By: Relevance
“…The testis interstitium harbors the steroidogenic Leydig cells, peritubular myoid cells, macrophages, vasculature, and other uncharacterized cell types such as fibroblasts and vascularassociated cells (Brennan and Capel, 2004;DeFalco et al, 2014). In the mouse, steroidogenic Leydig cells consist of two populations based on the time of their appearance: fetal and adult Leydig cells (Benton et al, 1995;Huhtaniemi and Pelliniemi, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The testis interstitium harbors the steroidogenic Leydig cells, peritubular myoid cells, macrophages, vasculature, and other uncharacterized cell types such as fibroblasts and vascularassociated cells (Brennan and Capel, 2004;DeFalco et al, 2014). In the mouse, steroidogenic Leydig cells consist of two populations based on the time of their appearance: fetal and adult Leydig cells (Benton et al, 1995;Huhtaniemi and Pelliniemi, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The ex vivo whole organ droplet method allows the researcher to administer pharmacological reagents easily to fetal organs in a very small volume of culture media. To examine the effects of vascularization and vascular remodeling on testis differentiation and morphogenesis, we used the small-molecule inhibitor TKI II, a reagent that disrupts testis vascular development 3 by blocking the activity of VEGF receptors; the formation of fetal testis architecture occurs in a vascular-dependent manner, acting through vascular endothelial growth factor A (VEGFA) 11,12 . While vascularization of the testis is critical for the export of testosterone that drives virilization of the embryo, it is also a major driver of testis cord morphogenesis: previous work has shown that when VEGFA signaling is blocked at or prior to E11.5, Sertoli cells fail to partition out from surrounding interstitial cells and no cord structures form 3,12 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…One significant advantage of culturing fetal gonads is that small-molecule inhibitors can readily access the whole organ by simple diffusion. DeFalco et al have shown that utilizing this ex vivo droplet culture method in conjunction with smallmolecule inhibitors can be used to study signaling processes and interactions occurring during gonad development 3 ; these processes would be difficult to examine in vivo due to technical challenges (e.g., passage of drugs through the placenta or lethality of affecting multiple organs using genetic or pharmacological approaches). .…”
Section: Introductionmentioning
confidence: 99%
“…The obvious differences between these two models was that mixed culture conditions allowed direct cellcell contact, whereas co-culture conditions allowed shared medium contact but considerable distance between fetal Leydig and remaining cells. Recently, other interstitial cells have emerged as critical players that together with endothelial cells organize testis morphogenesis and regulate fetal Leydig cell differentiation [22,57,58]. Thus, although our mixed culture system failed to recapitulate native cell-cell interactions, direct interactions were still present to facilitate more efficient conversion to testosterone.…”
Section: Maintenance Of Fetal Leydig Cell Activity Over Time In Culturementioning
confidence: 97%